2021
DOI: 10.1021/acs.chas.1c00041
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3-Dimensional Printers in Educational Settings: The Need for Awareness of the Effects of Printer Temperature and Filament Type on Contaminant Releases

Abstract: Material extrusion-type fused filament fabrication (FFF) 3-D printing is a valuable tool for education. During FFF 3-D printing, thermal degradation of the polymer releases small particles and chemicals, many of which are hazardous to human health. In this study, particle and chemical emissions from 10 different filaments made from virgin (never printed) and recycled polymers were used to print the same object at the polymer manufacturer’s recommended nozzle temperature (“normal”) and at a temperature higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
2
6
0
2
Order By: Relevance
“…Other commonly detected metals (in 5 to 6 out of the 8 samples) included Mg, Ca, Mn, Zn, As, Sr, Sn, and Pb ( Table 3 ). Previous studies reported metals commonly detected from PLA emitted particles included Fe, Zn, Si, K, Cu, Al, Na, Mg ( Steinle, 2016 ; Zontek et al, 2017 ; Stefaniak et al, 2017a; Youn et al, 2019 ; Stefaniak et al, 2021 ; Yi et al, 2019 ), which were also detected in this study, except for Fe. In addition, Na, Al and K were only detected in particles emitted from the two green PLA filaments ( Table 3 ).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Other commonly detected metals (in 5 to 6 out of the 8 samples) included Mg, Ca, Mn, Zn, As, Sr, Sn, and Pb ( Table 3 ). Previous studies reported metals commonly detected from PLA emitted particles included Fe, Zn, Si, K, Cu, Al, Na, Mg ( Steinle, 2016 ; Zontek et al, 2017 ; Stefaniak et al, 2017a; Youn et al, 2019 ; Stefaniak et al, 2021 ; Yi et al, 2019 ), which were also detected in this study, except for Fe. In addition, Na, Al and K were only detected in particles emitted from the two green PLA filaments ( Table 3 ).…”
Section: Resultssupporting
confidence: 76%
“…Of these, the extruder nozzle had the highest temperature ( Table 1 ). However, the extruder nozzle made of brass (printer D1 ) was unlikely to be a source of Cu and Zn in emitted particles due to the inconsistency of detection frequencies of these elements in the particles, i.e., neither Cu nor Zn was consistently detected from all particle samples emitted from printer D1 ; this was also suggested in a previous study ( Stefaniak et al, 2021 ). In addition, the build plate was heated for printer D1 (50 °C); the print chamber (i.e., where the printing process happened) was heated for printer E2 (80 °C); even without additional heating for printer E1 , the temperature inside the print chamber was also elevated since the printer is enclosed.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations